Educational Sustainability : An Integrated Analysis of Socioeconomic, Technological, and Environmental Impacts on Higher Education Students - Karthikeyan, K.; R., Maheswari; E., Dhanasekar; R., Gowrishankar; R., Ashok Kumar; M., Thomas Jeyanth Herbert (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study examined how higher education students perceived and engaged with sustainability across social, economic, technological, environmental, and educational dimensions. It identified key factors influencing the gap between awareness and actual behavior, which was crucial for fostering effective sustainability adoption. Methodology : A structural equation modeling (SEM) framework integrated multiple sustainability dimensions, analyzing social, economic, technological, environmental, and behavioral factors. Conducted in Coimbatore with 514 respondents, the study used percentage analysis, MANOVA, correlation, regression, factor analysis, and SEM to explore relationships shaping student engagement with sustainability. Findings : The study revealed a significant gap in comprehensive sustainability research, as many existing studies have examined individual dimensions in isolation. By integrating these aspects, the research highlighted key drivers and barriers to sustainability adoption, providing insights into improving student participation. Practical Implications : For policymakers, the study emphasized the need for targeted policies integrating sustainability into curricula. Educators can enhance learning through experiential and interdisciplinary approaches, fostering student participation in sustainability initiatives. Institutions should have promoted sustainability via green infrastructure, resource efficiency, and collaborations with industries and government agencies for real-world applications. Originality : Unlike fragmented studies, this research adopted a holistic framework to explore student perceptions and behaviors, offering multidimensional solutions for long-term sustainability impact in education.